Recognition dynamics of dopamine to human Monoamine oxidase B: role of Leu171/Gln206 and conserved water molecules in the active site cavity. Issue 6 (26th April 2018) - Dasgupta, Subrata; Mukherjee, Soumita; Mukhopadhyay, Bishnu P; Banerjee, Avik; Mishra, Deepak K
Abstract : The human Monoamine oxidase (hMAO) metabolizes several biogenic amine neurotransmitters and is involved in different neurological disorders. Extensive MD simulation studies of dopamine-docked hMAO B structures have revealed the stabilization of amino-terminal of the substrate by a direct and water-mediated interaction of catalytic tyrosines, Gln206, and Leu171 residues. The catechol ring of the substrate is stabilized by Leu171(C–H)⋯π(Dop)⋯(H–C) Ile199 interaction. Several conserved water molecules are observed to play a role in the recognition of substrate to the enzyme, where W1 and W2 associate in dopamine– FAD interaction, reversible dynamics of W3 and W4 influenced the coupling of Tyr435 to Trp432 and FAD, and W5 and W8 stabilized the catalytic Tyr188/398 residues. The W6, W7, and W8 water centers are involved in the recognition of catalytic residues and FAD with the N + - site of dopamine through hydrogen bonding interaction. The recognition of substrate to gating residues is made through W9, W10, and W11 water centers. Beside the interplay of water molecules, the catalytic aromatic cage has also been stabilized by π⋯water, π⋯C–H, and π⋯π interactions. The topology of conserved water molecular sites along with the hydration dynamics of catalytic residues, FAD, and dopamine has added a new feature on the substrate binding chemistry in hMAO B which may be useful for substrate analog inhibitor design.